2012
DOI: 10.1111/j.1445-2197.2012.06268.x
|View full text |Cite
|
Sign up to set email alerts
|

Penile fracture: second episode in 5 years

Abstract: Penile fracture: second episode in 5 yearsPenile fracture is a rare condition, accounting for 1 in 175 000 emergency presentations. 1 The most common cause is trauma during sexual intercourse, whereby the erect penis strikes the pubic symphysis or perineal body. It can be managed either surgically or conservatively. Gamal et al. reported 96% of patients treated with acute surgical repair achieving an erection adequate for intercourse, with no voiding dysfunction and no penile curvature versus 50% of those mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…All patients underwent the standardized surgical technique in our institution, as previously described ( 4 ), which consists of penile degloving through subcoronal incision. In this access, lesions of the corpora cavernosa are identified and the tunica albuginea is sutured with separate stitches of 3 - 0 Polyglactin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients underwent the standardized surgical technique in our institution, as previously described ( 4 ), which consists of penile degloving through subcoronal incision. In this access, lesions of the corpora cavernosa are identified and the tunica albuginea is sutured with separate stitches of 3 - 0 Polyglactin.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of a second episode of PF consists of an even rare situation, with only 10 cases described in the world literature ( 4 13 ). The aim of this study is to evaluate the demographic data, recurrence time, etiology and operative findings in the first and second episodes.…”
Section: Introductionmentioning
confidence: 99%
“…As previously discussed, reports in the literature include RF at the contralateral CC, 4 , 5 ipsilaterally at a new site, 6 , 7 and ipsilaterally at the same site. 8 , 9 Cases of same-site fracture, similar to the present case, foster the concept that, despite a complex healing process, final tissue resistance never reaches that of unwounded tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Recurrent PF is an exceedingly rare event, with very few reports in the literature. Recurrences can occur at different locations, including contralaterally, 4 , 5 ipisilaterally, 6 , 7 and at the same site. 8 , 9 This is, to the best of our knowledge, the 1st report of recurrent PF with 3 same-site recurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature review identified only nine cases of repetitive penile fractures. Seven of these repetitive fractures occurred on the ipsilateral corpus cavernosum, with just two cases occurring on the contralateral corpus 4,5,6,7,8,9,10,11,12 . An ipsilateral re-occurrence would suggest a fibrous scar liable to fracture on further insult, or possibly that the fibrous scar created a weaker contiguous tunica fascia prone to buckling when erect, and at pressures inferior to the usual stresses required to rupture normal albuginea.…”
Section: Repetitive Penile Fracture: a Case Reportmentioning
confidence: 99%